Fungal diversity of saprotrophic litter fungi in a Mediterranean maquis environment - Lunghini, D; Granito, V M; Di Lonardo, D P; Maggi, O; Persiani, A M (MYCOLOGIA, 2013)
Monospecific and mixed-leaf litters from plant species of Mediterranean maquis (Quercus ilex, Phillyrea angustifolia, Pistacia lentiscus, Cistus spp.) in an undisturbed area in southern Italy were studied with respect to the structure and composition of their decomposer fungal community over an incubation period of 403 d. The data matrix structure was analyzed by means of detrended correspondence analysis (DCA), while indicator species analysis (ISA) was used to determine the preferential association of species with a substrate, a succession phase and monospecific/mixed experimental conditions. The ecological nature of the gradient expressed by the DCA axes was investigated by means of experimental and main chemical leaf-litter variables. The litter mixture had non-additive effects on the decomposition process even though the fungal species richness of the mixed litter was considerably higher than that of the monospecific litter. Our findings highlight the occurrence of shifts in the fungal community during decomposition in response to changes in the substrate, such as those related to the cellulose content and lignin/N ratio.
Keywords: decomposition; fungal biodiversity; leaf-litter quality; Litter bags; Mediterranean maquis; monospecific/mixed litter

Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E.; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

POSTFIRE RESPROUTING OF SHRUBBY SPECIES IN MEDITERRANEAN MAQUIS - Gratani, L; AMADORI, M (VEGETATIO, 1991)
The vegetative resprouting of mediterranean maquis shrubby species was examined eight years after fire. Post-fire regeneration occurs through the resprouting of stumps. All species (Quercus ilex L., Phillyrea latifolia L., Arbutus unedo L., Erica arborea L., Pistacia lentiscus L.) show a rapid growth in the first years after fire, and a decrease already from 4th-5th year. All the species survived the fire and reconstituted a community similar to that unburned in a relatively short time span.
Keywords: fire; Mediterranean maquis; VEGETATIVE RESPROUTING

La Vegetazione del Parco del Conte (Ruvo di Puglia) - Scaramuzzi, Franca; Lorito, Fernanda (Giornale botanico italiano, 1953)
Summary The flora of a Quercus pubescens wood, near Ruvo di Puglia, has been studied. The presence of Pirus amygdaliformis, and of various weeds, together with the disappearence of some species like Bivonaea albiflora, indicate a certain amount of degradation due to grazing and cutting. The biological spectrum shows a noticeable abundance of therophytes (45%). The mixture of typical mediterranean «maquis» plants and of more mesophilous species suggests that at Ruvo the basal Quercus Ilex horizon finds its ecological boundary, Q. pubescens substituting green oak and decidous plants outbalancing evergreens.
doi: 10.1080/11263505309432122
Keywords: degradation; ecological boundary; floral composition; Mediterranean maquis; Ruvo di Puglia (PG)